A biocompatible supramolecular hydrogel with multivalent galactose ligands inhibiting Pseudomonas aeruginosa virulence and growth. Issue 56 (11th September 2020) - Liu, Shengnan; Li, Hang; Zhang, Jikun; Tian, Xin; Li, Xinming
Abstract : A glycopeptide hydrogel displaying galactoses on their surface was prepared, which inhibited Pseudomonas aeruginosa virulence and growth through multivalent interactions. Abstract : In recent years, peptide self-assembly proved to be an efficient strategy to create complex structures or functional materials with nanoscale precision. In this work, we designed and synthesized a novel glycopeptide molecule with a galactose moiety through peptide galactosylation. Then relying on peptide self-assembling strategies, we created a supramolecular hydrogel with multivalent galactose ligands on the surface of self-assembled nanofibers for molecular recognition and interactions. Because of multivalent galactose–LecA interactions, the self-assemblies of glycopeptide could target P. aeruginosa specifically, and acted as anti-virulence and antibacterial agents to inhibit biofilm formation and bacterial growth of P. aeruginosa . Moreover, in association with polymyxin B, a common antibiotic, the glycopeptide hydrogel exhibited a synergistic growth inhibition effect on biofilm colonization of P. aeruginosa .